Laboratory Static Hardness Tests - Wang, Hongwei (Nanyang Technological University, 2021)
The objective of laboratory static hardness tests is to perform mechanical testing to determine the available material hardness value. The hardness value is an important material property used in engineering design, analysis of structure, and materials development. This report will focus on the theory and experiment on how to determine the hardness value by Vickers hardness equipment as per American Society for Testing and Materials (ASTM) E92 testing standards and guidelines. After obtaining the Vickers hardness number, the report will provide hardness value to hardness value conversion table as per ASTM E140 standard. Hardness value to tensile strength conversion table as per International Organization for Standardization (ISO) 18625 Standard will also be used.